The Micro-Elimination Approach to Eliminating Hepatitis C: Strategic and Operational Considerations - Lazarus, Jeffrey V.; Safreed-Harmon, Kelly; Thursz, Mark R.; Dillon, John F.; El-Sayed, Manal H.; Elsharkawy, Ahmed M.; Hatzakis, Angelos; Jadoul, Michel; Prestileo, Tullio; Razavi, Homie; Rockstroh, Jürgen K.; Wiktor, Stefan Z.; Colombo, Massimo (Seminars in Liver Disease, 2018)
The introduction of efficacious new hepatitis C virus (HCV) treatments galvanized the World Health Organization to define ambitious targets for eliminating HCV as a public health threat by 2030. Formidable obstacles to reaching this goal can best be overcome through a micro-elimination approach, which entails pursuing elimination goals in discrete populations through multi-stakeholder initiatives that tailor interventions to the needs of these populations. Micro-elimination is less daunting, less complex, and less costly than full-scale, country-level initiatives to eliminate HCV, and it can build momentum by producing small victories that inspire more ambitious efforts. The micro-elimination approach encourages stakeholders who are most knowledgeable about specific populations to engage with each other and also promotes the uptake of new models of care. Examples of micro-elimination target populations include medical patients, people who inject drugs, migrants, and prisoners, although candidate populations can be expected to vary greatly in different countries and subnational areas.
Keywords: health policy; hepatitis C; micro-elimination; health systems; models of care